2002
DOI: 10.1046/j.1365-2893.2002.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus‐specific antibody titres in different phases of hepatitis C virus infection

Abstract: This study aimed to examine anti hepatitis C virus (HCV) antibody titres, their changes and differences in acute, chronic and past HCV infection and to examine them after IFN-alpha-therapy. Ninety five patients were studied in a cross-sectional investigation and 18 of them were followed long-term. Titres of IgM and IgG antibodies against core, NS3, NS4 (A + B), NS5A proteins were determined by the third generation enzyme immunoassays. Patients with acute hepatitis C developed IgG antibodies against core protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
4
28
1
Order By: Relevance
“…The anti-core titre of donors (Fig. 4b) in this study confirmed the data reported by Nikolaeva et al (2002), who showed a range of 1 : 800-1 : 40 000 of anti-core IgG titres in chronic HCV and an antibody titre value of 1 : 5-1 : 200 in a recovered group. Because of the lack of variation of high anti-HCV reactivity in donors chronically infected with different genotypes using the HCV 3.0 ELISA, it was unlikely that a reliable correlation between anti-F and anti-HCV could be found in terms of the S : CO ratio, even though a 4-4.5-fold greater seroreactivity of genotype 1 samples compared with genotype 2 or 3 was reported using a commercial assay (Dhaliwal et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…The anti-core titre of donors (Fig. 4b) in this study confirmed the data reported by Nikolaeva et al (2002), who showed a range of 1 : 800-1 : 40 000 of anti-core IgG titres in chronic HCV and an antibody titre value of 1 : 5-1 : 200 in a recovered group. Because of the lack of variation of high anti-HCV reactivity in donors chronically infected with different genotypes using the HCV 3.0 ELISA, it was unlikely that a reliable correlation between anti-F and anti-HCV could be found in terms of the S : CO ratio, even though a 4-4.5-fold greater seroreactivity of genotype 1 samples compared with genotype 2 or 3 was reported using a commercial assay (Dhaliwal et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…In a cohort of over 140 patients examined, 40% were found positive for the IgG anti-HCV core antibody, including 10% of individuals who were antibody non-reactive at the time of the first sample testing. This finding is quite intriguing given that the assay only evaluated antibody against a single N-terminal epitope (amino acids [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] of the core protein. Nevertheless, one may argue that the data are not entirely unexpected for a couple of reasons.…”
Section: See Article Pages 256-263mentioning
confidence: 99%
“…Nevertheless, one may argue that the data are not entirely unexpected for a couple of reasons. First, the core polypeptide, with several conserved epitope clusters, is thought to be the most immunogenic among the HCV proteins [14], and is able to elicit a more pronounced humoral response than the other HCV antigens in acute, chronic or resolved hepatitis C [15][16][17]. Second, in patients with resolved or progressing CHC, the most frequently identifiable antibodies are those directed against epitopes located towards the N-terminal half of the core protein [16], the same region Quiroga et al chose to study.…”
Section: See Article Pages 256-263mentioning
confidence: 99%
“…Other data, however, cast doubt on the role of these antibodies in the resolution of HCV infection [Cooper et al, 1999;Prince et al, 1999]. Few studies have examined the possible role of antibodies to the non-structural (NS) proteins and the results brought no clue [Bassett et al, 1998;Beld et al, 1999;Chen et al, 1999;Nikolaeva et al, 2002].…”
Section: Introductionmentioning
confidence: 99%